PENERAPAN MEDIA LATIHAN BERBASIS MODUL WIFI DALAM MENINGKATKAN ACCURACY PASSING DIHUBUNGKAN DENGAN METODE LATIHAN BOLABASKET - Hana Astria Nur; Gilang Lazuardi Hibatullah; Ramdhani Rahman (STKIP Muhammadiyah Kuningan, 2023)
Abstract ____________________________________________________________ In the world of sports, technology is a technical tool used by coaches and athletes to improve their training and competitive environment, to improve their overall performance. In basketball, technology-based training tool already exist that can only be used to train basic shooting techniques, but not for basic dribble and passing techniques. The purpose of this study is to create a wifi module-based training tool for use in special training such as accuracy passing training so as to produce increased accuracy especially in a passing. The method used in this study is a type of research development but continued with experimental research methods. The sample in this study is students who were members of UPI men's basketball team. The result indicate that the wifi module-based training tool is appropriate and there is an increase in the pretest and posttest scores in accuracy passing scores with the average pretest score 71.94 <80.88 posttest average score and the significance value of 0,000 <0.05. Therefore, this training tool can be used for periodic accuracy passing training.